2022
DOI: 10.1186/s40634-022-00544-1
|View full text |Cite|
|
Sign up to set email alerts
|

Fixed-loop vs. adjustable-loop cortical button devices for femoral fixation in ACL reconstruction – a systematic review and meta-analysis

Abstract: Purpose Button implants with either a fixed-loop device (FLD) or adjustable-loop device (ALD) are used frequently in Anterior Cruciate Ligament Reconstruction (ACLR). Since revision ACLR is associated with poorer clinical outcomes, it is important to investigate the difference in risk of revision between FLDs and ALDs. Therefore, this paper aims to systematically assess the risk of revision ACLR between ALDs and FLDs as well as secondary outcomes such as knee stability and patient reported outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“… 13 , 27 , 39 A systematic review and meta-analysis concluded that the scarce evidence suggests no difference in knee stability and subjective knee function between ALB and CLB. 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 27 , 39 A systematic review and meta-analysis concluded that the scarce evidence suggests no difference in knee stability and subjective knee function between ALB and CLB. 14 …”
Section: Discussionmentioning
confidence: 99%
“…13,27,39 A systematic review and meta-analysis concluded that the scarce evidence suggests no difference in knee stability and subjective knee function between ALB and CLB. 14 In previous generations of ALB, different approaches were presented to prevent slippage of the constructs and to improve primary stability. Retensioning of the ALB, as well as tying a knot over the button, after reaching the desired loop length has been shown to significantly reduce elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Tuy nhiên khả năng tự điều chỉnh của vòng treo góp phần rút ngắn thời gian cho cuộc mổ [8]. Một nghiên cứu phân tích tổng hợp trên 2686 bệnh nhân qua 15 báo cáo cho thấy chưa tìm thấy sự khác biệt có ý nghĩa thống kê giữa kết quả sau phẫu thuật tái tạo dây chằng có sử dụng vòng treo có điều chỉnh và vòng treo cố định ở ba nội dung là mức độ lỏng gối, tỷ lệ mổ lại và bảng tính toán kết quả lâm sàng được báo cáo của bệnh nhân (Patient reported outcome measures -PROMs) [7] [1]. Năm 2022, Trần Hoàng Tùng báo cáo nghiên cứu trên 32 BN thời gian theo dõi 5 năm với kích thước mảnh ghép DCCT và DCCS lần lượt là 9,29±0,77mm và 8,55±0,82mm đạt kết quả điểm Lysholm trung bình 89,7±6,7 điểm [5].…”
Section: Phương Tiện Cố địNh Mảnh Ghépunclassified
“…This erratum adds an abstract to the article Fixed-loop vs. adjustable-loop cortical button devices for femoral fixation in ACL reconstruction – a systematic review and meta-analysis [ 1 ]. The abstract was missing from the article version published 21 Oct 2022.…”
mentioning
confidence: 99%